A novel feedback loop between DYRK2 and USP28 regulates cancer homeostasis and DNA damage signaling - Suanes-Cobos, Lucía; Aguilera-Ventura, Irene; Torres-Ramos, Miguel; Serrano-Yubero, Alejandra; Moreno Fernández-Aliseda, Claudia; Fernández, Silvia; Garrido-Rodriguez, Martin; De la Luna, Susana; Prieto-Garcia, Cristian; Diefenbacher, Markus E.; Mejías-Pérez, Ernesto; Calzado, Marco A. (Cell death and differentiation, 2026)
Posttranslational modifications, such as ubiquitination and phosphorylation, play pivotal roles in regulating protein stability in response to cellular stress. Dual-specificity tyrosine phosphorylation-regulated kinase 2 (DYRK2) and ubiquitin-specific peptidase 28 (USP28) are critical regulators of cell cycle progression, DNA damage response, and oncogenic signaling. However, their functional interplay remains largely unexplored. Here, we describe a novel bidirectional regulatory mechanism between DYRK2 and USP28 that integrates DNA damage response and ubiquitin-mediated protein degradation. We demonstrate that DYRK2 phosphorylates USP28, promoting its ubiquitination and proteasomal degradation in a kinase activity-independent manner, thereby contributing to the maintenance of oncogenic protein homeostasis. Conversely, USP28 functions as a deubiquitinase for DYRK2, stabilizing its protein levels and enhancing its kinase activity. Notably, we show that DYRK2 interacts and co-localizes with USP28, with the 521-541 DYRK2 region, particularly residue T525, playing a crucial role in USP28-mediated DYRK2 stabilization. Functionally, this reciprocal regulation modulates p53 signaling, influencing apoptotic responses to DNA damage. DYRK2-mediated phosphorylation of p53 at S46 is significantly reduced upon USP28 depletion, suggesting that USP28 facilitates DYRK2-dependent apoptosis. Additionally, our results highlight a complex regulatory axis involving USP28 and DYRK2, with implications for oncogenic cell death and genomic stability. Overall, our findings uncover a novel feedback loop in which DYRK2 and USP28 dynamically regulate each other to control proto-oncoprotein homeostasis and DNA damage signaling. This interplay offers potential therapeutic opportunities for targeting cancers with dysregulated ubiquitination and genomic instability.
Online veröffentlicht: 26. August 2025
Gesehen am 25.02.2026